Preparation method of high-performance polyphenyl ether heat-conducting composite material
By modifying graphene and modified carbon fiber hybrid structures, the problems of low thermal conductivity and difficult processing of polyphenylene ether materials are solved, and the preparation of high-performance thermal conductivity composite materials is realized, which improves the thermal conductivity and mechanical properties of the materials, and simplifies the processing process.
Patent Information
- Application Number
- CN202510523579.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-08-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyphenylene ether materials have low thermal conductivity. While improving thermal conductivity, traditional thermal fillers will affect the mechanical properties and processing and forming properties of the materials. The preparation method is complex, costly and unenvironmental.
The modified graphene and modified carbon fiber hybrid structure are adopted, and ultrasonic dispersion and twin screw extrusion granulation are used, combined with chemical modification treatment, and the hierarchical structure of graphene-coated carbon fiber is formed, which enhances the interface binding force and dispersion uniformity, and achieves the coordinated improvement of thermal conductivity and mechanical properties.
The thermal conductivity and mechanical properties of polyphenylene ether thermal conductivity composite materials are improved, while reducing processing difficulty, achieving easy forming and efficient dispersion of the material.
Smart Images

Figure BDA0005374660650000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials, and particularly relates to a preparation method of a high-performance polyphenylene ether thermal conductive composite material. Background Art
[0002] Polyphenylene ether, with the chemical name of poly(2,6-dimethyl-1,4-phenylene ether), also known as polyphenylene oxide, abbreviated as PPO, has excellent mechanical strength, stress relaxation resistance, creep resistance, weather resistance, water resistance, dimensional stability, etc., and has good dielectric properties within a wide temperature and frequency range. Such excellent properties make polyphenylene ether have great application value in actual production. However, its low thermal conductivity limits its application in some occasions with high heat dissipation requirements. To improve the thermal conductivity of polyphenylene ether, thermal conductive fillers are often added to prepare polyphenylene ether thermal conductive composite materials. Although traditional thermal conductive fillers such as metal powders and ceramic particles can improve the thermal conductivity of the composite material to a certain extent, they often have an adverse impact on the mechanical properties and processing and molding properties of the material. At the same time, some preparation methods have problems such as complex process, high cost, and environmental unfriendliness.
[0003] For example, the prior art CN108997744B discloses a thermal conductive and insulating polyamide polyphenylene ether alloy material and its preparation method. The present invention discloses a thermal conductive and insulating polyamide polyphenylene ether alloy material, which includes the following components in parts by weight: PA6: 20 - 60 parts, PA6T: 10 - 20 parts, polyphenylene ether: 10 - 30 parts, compatibilizer: 3 - 7 parts, graphene-dispersed polymer powder: 3 - 15 parts, aluminum nitride: 5 - 10 parts, alumina: 0 - 10 parts, carbon fiber: 3 - 7 parts, graphite powder: 5 - 10 parts, silane coupling agent: 0.5 - 1 part, lubricant: 0.05 - 0.3 part, antioxidant: 0.1 - 0.3 part. By adding graphene-dispersed polymer powder, the overall compatibility and thermal conductivity are improved. The graphene-dispersed polymer powder uses styrene and caprolactam as carriers to load graphene, which can be used as a compatibilizer for inorganic materials and polymer materials. In addition, it can also improve the thermal conductivity of the material. This patent uses a variety of fillers with relatively high filling amounts, resulting in poor fluidity and great processing difficulty of the composite material. Therefore, it is of great significance to develop a polyphenylene ether thermal conductive composite material with excellent mechanical properties, thermal conductivity, and processing and molding properties. Summary of the Invention
[0004] The purpose of the present invention is to address the existing problems and provide a preparation method of a high-performance polyphenylene ether thermal conductive composite material.
[0005] The present invention is achieved through the following technical solutions:
[0006] A preparation method of a high-performance polyphenylene ether thermal conductive composite material includes the following steps:
[0007] S1. Ultrasonically disperse modified graphene and modified carbon fiber in deionized water according to a mass ratio of 3 - 4:1, and perform heat treatment at 100 °C for 0.5 - 1 h to form a Gn-CF hybrid.
[0008] S2. Add MPPO, SEBS and the Gn-CF hybrid into a twin-screw extruder for extrusion granulation to obtain granular materials.
[0009] S3. Dry the granular materials and then place them in an injection molding machine for molding.
[0010] Furthermore, the preparation of the modified graphene in step S1 includes the following steps:
[0011] (1) Prepare a mixed acid by mixing concentrated sulfuric acid and concentrated nitric acid according to a volume ratio of 3 - 4:1, then add graphene, perform ultrasonic treatment at 300 - 400 W for 1 - 2 h, pour the reaction solution into ice water, and perform centrifugal separation at 8000 - 10000 r / min. The solid product is centrifugally washed with deionized water 3 - 5 times and then dried to constant weight to obtain pre-oxidized graphene.
[0012] (2) Ultrasonically disperse the pre-oxidized graphene in N,N-dimethylformamide (DMF) to form a dispersion with a mass fraction of 2%, then add EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride) and NHS (N-hydroxysuccinimide), stir and react at room temperature for 10 - 12 h to activate the carboxyl groups on the surface of graphene, then add an amino-functionalized RAFT chain transfer agent and continue to stir and react for 10 - 12 h. After the reaction is completed, centrifuge at 8000 - 10000 r / min, wash with DMF and then dry to obtain activated graphene.
[0013] (3) Stir and mix toluene and N,N-dimethylformamide according to a volume ratio of 7:3 to obtain a mixed solvent, add it to a three-necked flask, then add the activated graphene, ultrasonically disperse it evenly, add polystyrene-b-poly(glycidyl methacrylate), and at the same time add a RAFT reagent, stir and mix evenly, then place the three-necked flask in an oil bath at 60 - 70 °C, react at 200 - 300 r / min for 1 - 2 h, then raise the temperature to 85 °C, and at this temperature, stir and react at 200 - 300 r / min for 2 - 3 h, then perform suction filtration, wash with ethanol 3 - 5 times and then dry to constant weight.
[0014] Furthermore, the mass-volume ratio of the graphene to the mixed acid in step (1) is 1 g:50 - 60 mL.
[0015] Furthermore, the molar ratios of EDC, NHS to the carboxyl groups on the surface of graphene in step (2) are 2:1 and 2:1 respectively.
[0016] The molar ratio of the amino-functionalized RAFT chain transfer agent to the activated carboxyl groups is 1:1.
[0017] Further, the mass-volume ratio of the activated graphene to the mixed solvent is 1 g: 20-30 mL;
[0018] The mass ratio of polystyrene-b-poly(glycidyl methacrylate) to the activated graphene is 1:1;
[0019] The molar ratio of the RAFT reagent to polystyrene-b-poly(glycidyl methacrylate) is 1:10-12.
[0020] Further, the preparation of the modified carbon fiber in step S1 includes the following steps:
[0021] 1) Place the chopped carbon fiber (CF) in a plasma reaction chamber, introduce an Ar / O2 mixed gas, treat it at 50-80 W for 3-5 min, and then irradiate it with ultraviolet ozone for 10-12 min to obtain activated carbon fiber;
[0022] 2) Add the activated carbon fiber to a high-pressure reaction, inject supercritical CO2, add 3-aminopropyltriethoxysilane (APTES) (3% of the mass of CO2), raise the temperature to 40-50 °C, increase the pressure to 10 MPa, and maintain the CO2 fluid state for 30-40 min. After completion, filter out the amino-functionalized carbon fiber;
[0023] 3) Prepare an ethanol solution of 5 wt% mercaptopropyltrimethoxysilane (MPTES), immerse the amino-functionalized carbon fiber in it, reflux at 60-70 °C for 1-2 h, then filter by suction, wash it with ethanol 3-5 times, and dry it to a constant weight.
[0024] Further, the length of the chopped carbon fiber in step 1) is 50-200 μm;
[0025] The Ar / O2 mixed gas is 20 mL / min O2 + 80 mL / min Ar;
[0026] The wavelength during ultraviolet irradiation is 254 nm and the power is 30 W.
[0027] Further, the molar ratio of the 3-aminopropyltriethoxysilane to the mercaptopropyltrimethoxysilane is 1:1.
[0028] Further, the mass ratio of MPPO, SEBS, and the Gn-CF hybrid in step S2 is 70-85:5-15:10-30;
[0029] During extrusion granulation, zone temperature control is carried out: zone 1 at 220 °C, zone 2 at 260 °C, zone 3 at 240 °C, and the screw speed is 180 r / min.
[0030] Further, during the injection molding in step S3, the barrel temperature is controlled at 260 - 280 °C, the holding pressure is 70 MPa, and the cooling time is 20 - 30 s.
[0031] The present invention has the following advantages compared with the prior art:
[0032] 1. Through the design of the graphene-carbon fiber hybrid structure and the collaborative optimization of the multiphase interface, the present invention realizes the collaborative breakthrough of the thermal conductivity, mechanical properties, and processing performance of the polyphenylene ether composite material. First, the modified graphene and modified carbon fiber are constructed into a hybrid under the action of ultrasonic waves according to a certain mass ratio. The pre-construction of the hybrid effectively avoids the agglomeration of the fillers. The uniform dispersion of the hybrid reduces the melt viscosity, and combined with the high-shear plasticization of the twin-screw extruder, it is easy to process and form. Graphene forms a covalent bond connection with the surface amino-functionalized carbon fiber through the epoxy groups grafted on the surface, and the hierarchical structure of "graphene-coated carbon fiber" can effectively improve the mechanical properties, thermal conductivity, and processing and forming performance of the polyphenylene ether thermal conductive composite material.
[0033] 2. Through mixed acid treatment and ultrasonic dispersion, a large number of carboxyl and hydroxyl groups are introduced on the surface of graphene, which can effectively reduce the agglomeration of the fillers and enhance the interfacial bonding with the matrix through the interaction of chemical bonds. After activating the carboxyl groups with DEC / NHS and grafting the amino-functionalized RAFT chain transfer agent (CTA-NH2), adjustable active sites are formed on the surface of graphene, providing a directional anchoring point for subsequent polymer grafting and avoiding the interfacial defects caused by random grafting. Immediately afterwards, the block copolymer polystyrene-b-poly(glycidyl methacrylate) (PS-b-PGMA) is grafted onto the surface of graphene. The PS segment (non-polar) has good compatibility with the PPO matrix (non-polar), which can reduce phase separation and further improve the dispersion uniformity of the fillers in the matrix, so that the heat conduction carriers are more easily transferred through the interface, thereby enhancing the thermal conductivity of the composite material. The PGMA segment (containing epoxy groups) can act as a "bridge" and combine with the PPO matrix, carbon fiber, SEBS, etc. through epoxy ring-opening reaction or polar interaction to enhance the interfacial adhesion force. In addition, the three-step modification of pre-oxidation, active site anchoring, and block copolymer reconstruction endows graphene with multiple functions of "polar group anchoring-flexible chain segment compatibilization-reactive group crosslinking", which can not only improve the thermal conductivity but also enhance the mechanical properties of the composite material.
[0034] 3. In the preparation of the carbon fiber of the present invention, through the plasma-assisted activation and supercritical CO2 step-by-step grafting technology, the green and efficient dual-functionalization of the carbon fiber is realized, and the dual functional groups synergistically enhance the chemical bonding with the matrix resin. Specific Embodiments
[0035] For a further explanation of the present invention, the following specific embodiments are described below.
[0036] Example 1
[0037] A preparation method of a high-performance polyphenylene ether thermal conductive composite material comprises the following steps:
[0038] S1. Ultrasonically disperse modified graphene and modified carbon fiber in deionized water according to a mass ratio of 3:1, and perform heat treatment at 100 °C for 0.5 h to form a Gn-CF hybrid;
[0039] The preparation of the modified graphene comprises the following steps:
[0040] (1) Prepare a mixed acid by mixing concentrated sulfuric acid and concentrated nitric acid according to a volume ratio of 3:1, then add graphene. The mass-volume ratio of graphene to the mixed acid is 1 g:50 mL. After ultrasonic treatment at 300 W for 1 h, pour the reaction solution into ice water, and centrifuge at 8000 r / min. The solid product is centrifugally washed 3 times with deionized water and then dried to constant weight to obtain pre-oxidized graphene;
[0041] (2) Ultrasonically disperse the pre-oxidized graphene in DMF to form a dispersion with a mass fraction of 2%. Then add EDC and NHS. The molar ratios of EDC, NHS to the carboxyl groups on the graphene surface are 2:1 and 2:1 respectively. Stir and react at room temperature for 10 h to activate the carboxyl groups on the graphene surface. Then add an amino-functionalized RAFT chain transfer agent. The molar ratio of the amino-functionalized RAFT chain transfer agent to the activated carboxyl groups is 1:1. Continue to stir and react for 10 h. After the reaction, centrifuge at 8000 r / min, wash with DMF and then dry to obtain activated graphene;
[0042] (3) Stir and mix toluene and dimethylformamide according to a volume ratio of 7:3 to obtain a mixed solvent. The mass-volume ratio of the activated graphene to the mixed solvent is 1 g:20 mL. Add it to a three-necked flask, then add the activated graphene. After ultrasonic dispersion, add polystyrene-b-poly(glycidyl methacrylate). The mass ratio of polystyrene-b-poly(glycidyl methacrylate) to the activated graphene is 1:1. At the same time, add a RAFT reagent. The molar ratio of the RAFT reagent to polystyrene-b-poly(glycidyl methacrylate) is 1:10. After stirring and mixing evenly, place the three-necked flask in an oil bath, react at 60 °C and 200 r / min for 1 h, then raise the temperature to 85 °C. At this temperature, stir and react at 200 r / min for 2 h, then perform suction filtration, wash 3 times with ethanol and then dry to constant weight;
[0043] The preparation of the modified carbon fiber comprises the following steps:
[0044] 1) Place CF (50 μm) in a plasma reaction chamber, introduce an Ar / O2 mixed gas (20 mL / min O2 + 80 mL / min Ar), treat it at 50 W for 3 min, and then irradiate it with ultraviolet ozone (254 nm, power 30 W) for 10 min to obtain activated carbon fiber;
[0045] 2) Add the activated carbon fiber to a high-pressure reaction, inject supercritical CO2, add APTES (3% of the mass of CO2), heat up to 40 °C, increase the pressure to 10 MPa, maintain the CO2 fluid state for 30 min, and filter out the amino-functionalized carbon fiber after completion;
[0046] 3) Prepare an ethanol solution of 5 wt% MPTES, with a molar ratio of APTES to MPTES of 1:1. Immerse the amino-functionalized carbon fiber in it, reflux at 60 °C for 1 h, then perform suction filtration, wash it 3 times with ethanol, and dry it to a constant weight;
[0047] S2. Add MPPO, SEBS, and the Gn-CF hybrid in a mass ratio of 70:5:10 to a twin-screw extruder for extrusion granulation to obtain pellets. During granulation, control the temperature in different zones: zone 1 at 220 °C, zone 2 at 260 °C, zone 3 at 240 °C, and the screw speed at 180 r / min;
[0048] S3. Dry the pellets and then place them in an injection molding machine for molding. During injection molding, control the barrel temperature at 260 °C, the holding pressure at 70 MPa, and the cooling time at 20 s.
[0049] Example 2
[0050] A preparation method of a high-performance polyphenylene ether thermal conductive composite material, comprising the following steps:
[0051] S1. Ultrasonically disperse modified graphene and modified carbon fiber in deionized water at a mass ratio of 3.5:1, and perform heat treatment at 100 °C for 0.75 h to form a Gn-CF hybrid;
[0052] The preparation of the modified graphene includes the following steps:
[0053] (1) Prepare a mixed acid by mixing concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3.5:1, then add graphene, with a mass-volume ratio of graphene to the mixed acid of 1 g:55 mL. After ultrasonic treatment at 350 W for 1.5 h, pour the reaction solution into ice water, centrifuge and separate at 9000 r / min, and wash the solid product 4 times by centrifugation with deionized water and then dry it to a constant weight to obtain pre-oxidized graphene;
[0054] (2) Ultrasonically disperse the pre-oxidized graphene in DMF to form a dispersion with a mass fraction of 2%, then add EDC and NHS. The molar ratios of EDC and NHS to the carboxyl groups on the graphene surface are 2:1 and 2:1 respectively. Stir and react at room temperature for 11 h to activate the carboxyl groups on the graphene surface. Then add the amino-functionalized RAFT chain transfer agent. The molar ratio of the amino-functionalized RAFT chain transfer agent to the activated carboxyl groups is 1:1. Continue to stir and react for 11 h. After the reaction is completed, centrifuge at 9000 r / min, wash with DMF, and dry to obtain the activated graphene;
[0055] (3) Stir and mix toluene and dimethylformamide according to a volume ratio of 7:3 to obtain a mixed solvent. The mass-to-volume ratio of the activated graphene to the mixed solvent is 1 g:25 mL. Add it to a three-necked flask, and then add the activated graphene. After ultrasonic dispersion, add polystyrene-b-poly(glycidyl methacrylate). The mass ratio of polystyrene-b-poly(glycidyl methacrylate) to the activated graphene is 1:1. At the same time, add the RAFT reagent. The molar ratio of the RAFT reagent to polystyrene-b-poly(glycidyl methacrylate) is 1:11. After stirring and mixing evenly, place the three-necked flask in an oil bath. React at 65 °C and 250 r / min for 1.5 h, then raise the temperature to 85 °C. At this temperature, stir and react at 250 r / min for 2.5 h, then perform suction filtration, wash 4 times with ethanol, and dry to constant weight;
[0056] The preparation of the modified carbon fiber includes the following steps:
[0057] 1) Place CF (100 μm) in a plasma reaction chamber, introduce an Ar / O2 mixed gas (20 mL / min O2 + 80 mL / min Ar), treat at 60 W for 4 min, and then irradiate with ultraviolet ozone (254 nm, power of 30 W) for 11 min to obtain the activated carbon fiber;
[0058] 2) Add the activated carbon fiber to a high-pressure reaction, inject supercritical CO2, add APTES (3% of the mass of CO2), raise the temperature to 45 °C, raise the pressure to 10 MPa, maintain the CO2 fluid state for 35 min, and after completion, filter out the amino-functionalized carbon fiber;
[0059] 3) Prepare an ethanol solution of 5 wt% MPTES. The molar ratio of APTES to MPTES is 1:1. Immerse the amino-functionalized carbon fiber in it, reflux at 65 °C for 1.5 h, then perform suction filtration, wash 4 times with ethanol, and dry to constant weight;
[0060] S2. Add MPPO, SEBS and the Gn-CF hybrid into a twin-screw extruder according to a mass ratio of 75:10:15 to perform extrusion granulation to obtain granular materials. During granulation, control the temperature in different zones: zone 1 at 220 °C, zone 2 at 260 °C, zone 3 at 240 °C, and the screw speed is 180 r / min;
[0061] S3. After drying the granular materials, place them in an injection molding machine for molding. When injection molding, control the barrel temperature at 270 °C, the holding pressure at 70 MPa, and the cooling time at 25 s.
[0062] Example 3
[0063] A preparation method of a high-performance polyphenylene ether thermal conductive composite material, comprising the following steps:
[0064] S1. Ultrasonically disperse modified graphene and modified carbon fiber into deionized water according to a mass ratio of 4:1, and perform heat treatment at 100 °C for 1 h to form a Gn-CF hybrid;
[0065] The preparation of the modified graphene comprises the following steps:
[0066] (1) Prepare a mixed acid by mixing concentrated sulfuric acid and concentrated nitric acid according to a volume ratio of 4:1, then add graphene. The mass-volume ratio of graphene to the mixed acid is 1 g:60 mL. After ultrasonic treatment at 400 W for 2 h, pour the reaction solution into ice water, and centrifuge at 10,000 r / min. The solid product is centrifugally washed with deionized water 5 times and then dried to constant weight to obtain pre-oxidized graphene;
[0067] (2) Ultrasonically disperse the pre-oxidized graphene into DMF to form a dispersion with a mass fraction of 2%. Then add EDC and NHS. The molar ratios of EDC, NHS to the carboxyl groups on the graphene surface are 2:1 and 2:1 respectively. Stir and react at room temperature for 12 h to activate the carboxyl groups on the graphene surface. Then add an amino-functionalized RAFT chain transfer agent. The molar ratio of the amino-functionalized RAFT chain transfer agent to the activated carboxyl groups is 1:1, and continue to stir and react for 12 h. After the reaction, centrifuge at 10,000 r / min, wash with DMF and then dry to obtain activated graphene;
[0068] (3) Mix toluene and dimethylformamide in a volume ratio of 7:3 and stir evenly to obtain a mixed solvent. The mass-to-volume ratio of activated graphene to the mixed solvent is 1 g:20 - 30 mL. Add it to a three-necked flask, and then add activated graphene. After ultrasonic dispersion, add polystyrene-b-poly(glycidyl methacrylate). The mass ratio of polystyrene-b-poly(glycidyl methacrylate) to activated graphene is 1:1. At the same time, add a RAFT reagent. The molar ratio of the RAFT reagent to polystyrene-b-poly(glycidyl methacrylate) is 1:12. After stirring evenly, place the three-necked flask in an oil bath, react at 70 °C and 300 r / min for 2 h, then raise the temperature to 85 °C. At this temperature, stir and react at 300 r / min for 3 h, then filter by suction, wash with ethanol 5 times, and dry to constant weight;
[0069] The preparation of the modified carbon fiber includes the following steps:
[0070] 1) Place CF (200 μm) in a plasma reaction chamber, introduce an Ar / O2 mixed gas (20 mL / min O2 + 80 mL / min Ar), treat at 80 W for 5 min, and then irradiate with ultraviolet ozone (254 nm, power 30 W) for 12 min to obtain activated carbon fiber;
[0071] 2) Add the activated carbon fiber to a high-pressure reaction, inject supercritical CO2, add APTES (3% of the mass of CO2), raise the temperature to 50 °C, increase the pressure to 10 MPa, and maintain the CO2 fluid state for 40 min. After completion, filter out the amino-functionalized carbon fiber;
[0072] 3) Prepare an ethanol solution of 5 wt% MPTES. The molar ratio of APTES to MPTES is 1:1. Immerse the amino-functionalized carbon fiber in it, reflux at 70 °C for 2 h, then filter by suction, wash with ethanol 5 times, and dry to constant weight;
[0073] S2. Add MPPO, SEBS, and the Gn-CF hybrid in a mass ratio of 85:15:30 to a twin-screw extruder for extrusion granulation to obtain pellets. During granulation, control the temperature in different zones: zone 1 at 220 °C, zone 2 at 260 °C, zone 3 at 240 °C, and the screw speed is 180 r / min;
[0074] S3. Dry the pellets and then place them in an injection molding machine for molding. When injection molding, control the barrel temperature at 280 °C, the holding pressure at 70 MPa, and the cooling time at 30 s.
[0075] Comparative Example 1
[0076] On the basis of Example 2, replace the modified graphene with untreated graphene, and the other technical solutions are the same as those in Example 2.
[0077] Comparative Example 2
[0078] On the basis of Example 2, the modified carbon fiber was replaced with untreated carbon fiber, and the rest of the technical solutions were the same as those in Example 2.
[0079] Performance Testing and Characterization
[0080] High-performance polyphenylene ether thermal conductive composites were respectively prepared by the methods of Examples 1 to 3 and Comparative Examples 1 to 2 above, and then performance testing was carried out.
[0081] (1) Tensile Strength:
[0082] The tensile strength was measured by an electronic universal testing machine, and the test standard referred to GB-T1040.1-2-2006. The test parameters were: gauge length 50 mm, width 10 mm, thickness 4 mm, and test speed 20 mm / min.
[0083] (2) Impact Strength:
[0084] The impact strength was measured by a simple supported beam pendulum impact testing machine, and the test standard referred to GB-T1043.1. The test parameters were: thickness 4 mm, width 10 mm, notch depth 2 mm, and cross-sectional area 32 mm 2 .
[0085] (3) Thermal Conductivity:
[0086] The thermal conductivity was measured by the TCi thermal conductivity test method, also known as the "modified transient plane heat source method". This method is fast, simple, and highly accurate, and the test range is 0.01 to 100 W·m -1 ·K -1 , and the required specimen size was: diameter 22 mm, thickness 5 mm.
[0087] The test results of each performance are shown in Table 1 below.
[0088] Table 1
[0089]
[0090] It can be seen from Table 1 above that the mechanical properties and thermal conductivity of the composites prepared by the methods of Examples 1 to 3 are better than those of the comparative examples, indicating that the combined use of the modified graphene and modified carbon fiber of the present invention has a good improvement effect on the thermal conductivity, mechanical properties, and processing properties of the composites.
[0091] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and should be covered within the protection scope of the present invention.
Claims
1. A preparation method of a high-performance polyphenylene ether thermal conductive composite material, characterized in that, It includes the following steps: S1. Ultrasonically disperse modified graphene and modified carbon fiber in deionized water according to a mass ratio of 3-4:1, and perform heat treatment at 100 °C for 0.5-1 h to form a Gn-CF hybrid; S2. Add MPPO, SEBS and the Gn-CF hybrid into a twin-screw extruder for extrusion granulation to obtain granular materials; S3. Dry the granular materials and then place them in an injection molding machine for molding.
2. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 1, characterized in that, The preparation method of the modified graphene described in step S1 includes the following steps: (1) Prepare a mixed acid by mixing concentrated sulfuric acid and concentrated nitric acid according to a volume ratio of 3-4:1, then add graphene, perform ultrasonic treatment at 300-400 W for 1-2 h, pour the reaction solution into ice water, and centrifuge at 8000-10000 r / min. The solid product is centrifugally washed with deionized water 3-5 times and then dried to constant weight to obtain pre-oxidized graphene; (2) Ultrasonically disperse the pre-oxidized graphene in N,N-dimethylformamide to form a dispersion with a mass fraction of 2%, then add 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, stir and react at room temperature for 10-12 h to activate the carboxyl groups on the surface of graphene, then add an amino-functionalized RAFT chain transfer agent, and continue to stir and react for 10-12 h. After the reaction, centrifuge at 8000-10000 r / min, wash with N,N-dimethylformamide and then dry to obtain activated graphene; (3) Stir and mix toluene and N,N-dimethylformamide according to a volume ratio of 7:3 to obtain a mixed solvent, add it to a three-necked flask, then add activated graphene, ultrasonically disperse it evenly, add polystyrene-b-poly(glycidyl methacrylate), and at the same time add a RAFT reagent, stir and mix evenly, then place the three-necked flask in an oil bath at 60-70 °C, react at 200-300 r / min for 1-2 h, then raise the temperature to 85 °C, and at this temperature, stir and react at 200-300 r / min for 2-3 h, then perform suction filtration, wash with ethanol 3-5 times and then dry to constant weight.
3. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 2, characterized in that, The mass-volume ratio of the graphene to the mixed acid described in step (1) is 1 g:50-60 mL.
4. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 2, wherein The molar ratios of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide to the carboxyl groups on the surface of graphene described in step (2) are 2:1 and 2:1 respectively; The molar ratio of the amino-functionalized RAFT chain transfer agent to the activated carboxyl groups is 1:
1.
5. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 2, wherein, The mass-volume ratio of the activated graphene to the mixed solvent is 1 g:20-30 mL; The mass ratio of polystyrene-b-poly(glycidyl methacrylate) to the activated graphene is 1:1; The molar ratio of the RAFT reagent to polystyrene-b-poly(glycidyl methacrylate) is 1:10-12.
6. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 1, wherein The preparation method of the modified carbon fiber described in step S1 includes the following steps: 1) Place the chopped carbon fiber in a plasma reaction chamber, introduce an Ar / O2 mixed gas, treat it at 50-80 W for 3-5 min, and then irradiate it with ultraviolet ozone for 10-12 min to obtain activated carbon fiber; 2) Add activated carbon fiber into a high-pressure reaction, inject supercritical CO2, add 3-aminopropyltriethoxysilane, heat up to 40 - 50 °C, increase the pressure to 10 MPa, maintain the CO2 fluid state for 30 - 40 min, and filter out the aminated carbon fiber after completion; 3) Prepare an ethanol solution of 5 wt% mercaptopropyltrimethoxysilane, immerse the aminated carbon fiber in it, reflux at 60 - 70 °C for 1 - 2 h, then perform suction filtration, wash with ethanol 3 - 5 times, and dry to constant weight.
7. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 6, characterized in that, The length of the chopped carbon fiber described in step 1) is 50 - 200 μm; The Ar / O2 mixed gas is 20 mL / min O2 + 80 mL / min Ar; When performing ultraviolet irradiation, the wavelength is 254 nm and the power is 30 W.
8. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 6, characterized in that, The molar ratio of the 3-aminopropyltriethoxysilane and mercaptopropyltrimethoxysilane is 1:
1.
9. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 1, characterized in that, The mass ratio of the MPPO, SEBS, and Gn-CF hybrid described in step S2 is 70 - 85:5 - 15:10 - 30; During extrusion granulation, zone temperature control is carried out: zone 1 at 220 °C, zone 2 at 260 °C, zone 3 at 240 °C, and the screw speed is 180 r / min.
10. The preparation method of a high-performance polyphenylene ether thermal conductive composite material according to claim 1, characterized in that, During injection molding described in step S3, control the barrel temperature at 260 - 280 °C, the holding pressure at 70 MPa, and the cooling time at 20 - 30 s.